The Use of Unbounded Utility Functions in Expected-Utility Maximization: Response - Arrow, Kenneth J. (Quarterly Journal of Economics, 1974)
Journal Article The Use of Unbounded Utility Functions in Expected-Utility Maximization: Response Get access Kenneth J. Arrow Kenneth J. Arrow Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 88, Issue 1, February 1974, Pages 136–138, https://doi.org/10.2307/1881800 Published: 01 February 1974